Clusterin regulates macrophage expansion, polarization and phagocytic activity in response to inflammation in the kidneys. Issue 3 (16th October 2020) - Weng, Xiaodong; Zhao, Haimei; Guan, Qiunong; Shi, Ganggang; Feng, Shijian; Gleave, Martin E; Nguan, Christopher CY; Du, Caigan
Abstract: Clusterin (CLU) is a multifunctional protein localized extracellularly and intracellularly. Although CLU‐knockout (KO) mice are more susceptible to renal ischemia‐reperfusion injury (IRI), the mechanisms underlying the actions of CLU in IRI are not fully understood. Macrophages are key regulators of IRI severity and tissue repair. Therefore, we investigated the role of CLU in macrophage polarization and phagocytosis. Renal IRI was induced in wild‐type (WT) or CLU‐KO C57BL/6 mice by clamping the renal pedicles for 30 min at 32°C. Peritoneal macrophages were activated via an intraperitoneal injection of lipopolysaccharide (LPS). Renal tissue damage was examined using histology, whereas leukocyte phenotypes were assessed using flow cytometry and immunohistochemistry. We found that monocytes/macrophages expressed the CLU protein that was upregulated by hypoxia. The percentages of macrophages (F4/80 +, CD11b + or MAC3 + ) infiltrating the kidneys of WT mice were significantly less than those in CLU‐KO mice after IRI. The M1/M2 phenotype ratio of the macrophages in WT kidneys decreased at day 7 post‐IRI when the injury was repaired, whereas that in KO kidneys increased consistently as tissue injury persisted. In response to LPS stimulation, WT mice produced fewer M1 macrophages, but not M2, than the control did. Phagocytosis was stimulated by CLU expression in macrophages compared with the CLU null controls and by the exogenous CLU protein. In conclusion, CLU suppresses macrophage infiltration and proinflammatory M1 polarization during the recovery period following IRI, and enhances phagocytic activity, which may be partly responsible for tissue repair in the kidneys of WT mice after injury. Abstract : In this study, we found that macrophages expressed clusterin, and knockout of clusterin expression disrupted the decrease of infiltrating macrophages and M2 polarization during the late stage of recovery after ischemia‐reperfusion injury in the kidney.